Localized Structural Alterations Underlying a Subset of Unexplained Sudden Cardiac Death. (July 2018) - Haïssaguerre, Michel; Hocini, Mélèze; Cheniti, Ghassen; Duchateau, Josselin; Sacher, Frédéric; Puyo, Stéphane; Cochet, Hubert; Takigawa, Masateru; Denis, Arnaud; Martin, Ruairidh; Derval, Nicolas; Bordachar, Pierre; et al.
Abstract : Background: Sudden cardiac death because of ventricular fibrillation (VF) is commonly unexplained in younger victims. Detailed electrophysiological mapping in such patients has not been reported. Methods: We evaluated 24 patients (29±13 years) who survived idiopathic VF. First, we used multielectrode body surface recordings to identify the drivers maintaining VF. Then, we analyzed electrograms in the driver regions using endocardial and epicardial catheter mapping during sinus rhythm. Established electrogram criteria were used to identify the presence of structural alterations. Results: VF occurred spontaneously in 3 patients and was induced in 16, whereas VF was noninducible in 5. VF mapping demonstrated reentrant and focal activities (87% versus 13%, respectively) in all. The activities were dominant in one ventricle in 9 patients, whereas they had biventricular distribution in others. During sinus rhythm areas of abnormal electrograms were identified in 15/24 patients (62.5%) revealing localized structural alterations: in the right ventricle in 11, the left ventricle in 1, and both in 3. They covered a limited surface (13±6 cm 2 ) representing 5±3% of the total surface and were recorded predominantly on the epicardium. Seventy-six percent of these areas were colocated with VF drivers ( P <0.001). In the 9 patients without structural alteration, we observed a high incidence of Purkinje triggers (7/9 versus 4/15, P =0.033). Catheter ablation resulted in arrhythmia-free outcome in 15/18 patients at 17±11 months follow-up. Conclusions: This study shows that localized structural alterations underlie a significant subset of previously unexplained sudden cardiac death. In the other subset, Purkinje electrical pathology seems as a dominant mechanism. Abstract : Supplemental Digital Content is available in the text.